Currículo: educação ambiental e gerenciamento de riscos em escolas próximas à Petrobras no município de Santos/SP - Going, Luana Carramillo (2011)
The research is based on studies on sustainability, environmental policy, social management of the risks generated by oil and gas on the network of oil and gas ducts of Petrobras. The goal is to gather and classify what academic studies in Postgraduate program and what projects were undertaken in schools with the participation of the Education Secretariat of the municipality of Santos/SP. It is necessary for appearing in this work be a project facing the environmental education and management risk followed by an emergency plan to protect the population living in the area and vicinity of the Petrobras oil ducts. The method employed is of qualitative research that performs bibliographic analysis of academic production in the period 2005-2010, post graduated and doctoral programs in the State of São Paulo and the analysis of survey of projects developed in elementary schools in the municipality of Santos. As the procedure we followed Bardin content analysis (1995) of selected theses and dissertations. Guiding the research we had three questions: a) is there a consciousness of planetary citizenship and professional commitment among those responsible for carrying out preventive measures for situations of risk both to the environmental integrity of school units? (b)) which curriculum involves interdisciplinary actions and reflections among education professionals and the community, on public policies and management of environmental risks? c) Is there a democratic management when educators and community dialogue on environmental education and management of risks? The result of research points out that 294 (66 theses and 228 master‟s thesis) were developed in postgraduate courses in Universities in the State of São Paulo. Twenty-seven (27) (three theses and 24 master‟s thesis) developed in master and doctoral programs in Education related to Santos district and 133 dissertations were developed in the program of master's degree in Education in Santos. When analyzing of contents of the researches, participation in projects submitted by researchers that do not work at school, in most cases, shows the participation of students without the involvement of teachers, otherwise, under observation research, the work produced in Educational Secretarial of the municipality of Santos/SP was the excellence of academic professional teams, projects focused on community diversity of each school unit and also there is concern in the training of teachers in teleteaching programs for environmental education. From the results, presented a Curriculum in Environmental education and risk management suggestion for the regions close to Petrobras oil ducts